2017
DOI: 10.3389/fonc.2017.00171
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Tumor Cell Invasion and Metastasis by Endoplasmic Reticulum-to-Mitochondrial Ca2+ Transfer

Abstract: Cell migration is one of the many processes orchestrated by calcium (Ca2+) signaling, and its dysregulation drives the increased invasive and metastatic potential of cancer cells. The ability of Ca2+ to function effectively as a regulator of migration requires the generation of temporally complex signals within spatially restricted microdomains. The generation and maintenance of these Ca2+ signals require a specific structural architecture and tightly regulated communication between the extracellular space, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 135 publications
2
33
0
Order By: Relevance
“…Metastasis is a multistep process involving a plethora of cellular adaptations. 25 Mitochondria, 26 Ca 2þ oscillations, 27 extracellular matrix degradation, 28 and the tumor microenvironment 29 have been shown to determine tumor malignancy and dissemination. Interestingly, we could detect changes in mitochondrial homeostasis with loss of 1 allele of Atg5.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is a multistep process involving a plethora of cellular adaptations. 25 Mitochondria, 26 Ca 2þ oscillations, 27 extracellular matrix degradation, 28 and the tumor microenvironment 29 have been shown to determine tumor malignancy and dissemination. Interestingly, we could detect changes in mitochondrial homeostasis with loss of 1 allele of Atg5.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ is mainly stored in ER lumen, which is a critical regulator involved in cancer progression 52 . Accumulating evidences indicate that transient elevation of intracellular Ca 2+ can promote tumor cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the up-regulation of both IP3R and MCU in several types of cancer cells, it seems that ER/mitochondria communication is key for increased mitochondrial metabolism and cancer progression (Bustos et al, 2017 ). VDAC1 expression is related to poor prognosis in breast, colon, and lung cancers, where it has been demonstrated that VDAC1 promotes cell growth by influencing energy metabolism and inhibiting apoptosis (Mazure, 2017 ; White, 2017 ). Additionally, pulmonary arterial cancer cells and colon cancer cells avoid [Ca 2+ ] m overload through downregulation of MCU, which confers resistance to cell death (Liu et al, 2017 ).…”
Section: Influence Of [Ca 2+ ] M mentioning
confidence: 99%